Early Detection and Rapid Response (EDRR) to Nonnative Wildlife in South Florida - Justin Dalaba; Frank Mazzotti (EDIS)
Invasive nonnative wildlife threaten successful restoration of Everglades ecosystems in south Florida. If nothing is done while an invasion is in the beginning stages, populations can grow and become much more difficult to manage, as happened with the Burmese pythons. This 4-page fact sheet written by Justin R. Dalaba and Frank J. Mazzotti and published by the UF/IFAS Wildlife Ecology and Conservation Department explains how the Early Detection and Rapid Response method works and how to apply it to increase the likelihood that an invasion will be successfully contained or eradicated while an invasive population is still small and localized. http://edis.ifas.ufl.edu/uw454